Impact of Employee Competence and Behaviour on Banking Customer Trust: Empirical Study in Saudi Arabia - Alhazemi, Abdulrahm A. (Archives of Business Research, 2023)
The main purpose of the study was to find out the impact of employee competence and employee behaviour on banking customers’ attitude towards banking and trust in the banking system. 300 responses were collected from banking customers by administering structured questionnaire developed for the purpose and translated into arabic language. The results of the study showed that employee competence positive relationship with employee behaviour, and customer attitudes, however it has no significant relationship with the banking customer trust. Employee behaviour has statistically significant relationship with attitude and trust. Customer’s attitude influence trust of the banking customer. The study makes significant contribution to the literature. The findings of the study are important for the banks to improve and enhance banking customer’s attitudes and trust through employee competence and behaviour.